(untitled) (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
The objectives of this study were to investigate the strategies used by the English teacher for teaching reading comprehension and to find out the reasons why teacher used those strategies in teaching reading comprehension of first grade students at SMK Swasta Tunas Karya Batang Kuis. This research used descriptive qualitative method. The subjects of this study were two English teachers who teach at SMK Swasta Tunas Karya Batang Kuis, Deli Serdang especially at first grade students. The instruments of this study were recording, interview and documentation. The findings found that, the first teacher used two strategies, Scaffolding and QARs (Question Answer Relationship). Scaffolding strategy student can develop about idea which readable by the student. QARs (Question Answer Relationship), the teacher able to know how far their students understand what the teacher has given to them. The second teacher used conventional strategy. This strategy should be selected based on its appropriateness and effectiveness to the learning process so that its use will enable the teacher to explore the students™ ideas and to help them read in a better way. Based on the analysis inteview, the reason why teachers used those types of strategies on students™ reading comprehension were because to make the student understand the reading text and the students guided to more focus on the text. To help their students overcome difficulties in comprehending the texts, especially the various aspects of reading such as the main idea, detailed information, making inferences and noting references and also teacher could help students in developing the meaning contained in the text reading so that students more easily understand the contents of reading. Keywords: Teachers™ Strategies, Reading Comprehension